Media and Language Use in the Omnibus Law Representation - Wilbert Christian; Trisnowati Tanto (Research Aspects in Arts and Social Studies Vol. 7, 2023)
This paper discusses how the media, in this case The Jakarta Post, represents the Omnibus Law in its article entitled “Omnibus Law Boosts Indonesian Growth Prospects”. The study mainly covers the micro level analysis, namely in the macrostructure, microstructure, and superstructure aspects using the qualitative descriptive research method and the library research method. In the macrostructure, the focus is on the headline and lead of the news article. In the microstructure, five linguistics tools, namely evidentiality, consensus, example/illustration, actor description, and number game, are employed in analyzing the data. In the superstructure, the text is divided into five different schematic categories so that the analysis can deal more with the organization of ideas. The findings show that in the macrostructure, the data constructs a global topic that “The Omnibus Law gives Indonesia some improvements in the economic aspect, especially in the business climate and labor market flexibility, in the hope of getting the international competitiveness,” which puts the law in a positive light. Moreover, through the use of five linguistics tools, the Omnibus Law is depicted positively. In terms of the superstructure, the comment category becomes the most prominent category used by the author, through which the positive representation of the Omnibus Law is revealed. Hence, the Omnibus Law’s positive representation is consistently seen through the macrostructure, microstructure, and superstructure aspects. Besides, the data appears to be subjective due to the dominant use of comments that conveys the author’s personal opinion.